PENGENDALIAN PENCEMARAN LINGKUNGAN DENGAN PENERAPAN TEKNOLOGI PROSES TERBAIK â€œBEST AVAILABLE TECHNIQUESâ€ UNTUK PRODUKSI AMONIAK - Djoko Wiwoho (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2000)
Best Available Techniques (BAT) is developed especially in the European Community, responding environmental issue by designing the process that the polluted chemicals released during the plant operation are still under the environmental tolerances. Beside environmentally friendly, the technology is also efficient and consumes less energy.